A retrospective analysis of the prevalence and impact of associated comorbidities on fibromyalgia outcomes in a tertiary care center - Rivera, Fernando A.; Munipalli, Bala; Allman, Madeleine E.; Hodge, David O.; Wieczorek, Mikolaj A.; Wang, Benjamin; Abril, Andy; Perlman, Adam; Knight, Dacre; Bruce, Barbara (Frontiers in Medicine, 2024)
Background This retrospective study was designed to analyze the prevalence and impact of associated comorbidities on fibromyalgia (FM) outcomes (functionality, pain, depression levels) for patients who participated in an intensive multicomponent clinical program in a tertiary care center. Methods Participants included a sample of 411 patients diagnosed with FM at a large tertiary medical center using the 2016 ACR criteria. Patients completed an intensive 2-day cognitive behavioral treatment (CBT) program, filled out the Fibromyalgia Impact Questionnaire Revised (FIQR), the Center for Epidemiologic Studies Depression Scale (CES-D), the Pain Catastrophizing Scale (PCS), and were followed for 6 months after treatment completion. T-tests were performed to analyze differences between the presence or absence of select comorbidities for the three outcomes at follow-up. Statistically significant comorbidities (p < 0.05) were used as predictors in multivariable logistic regression models. Results The FM associated comorbidities in this cohort that had significant impact on the measured outcome domains after treatment program completed were Obesity (FIQR p = 0.024), Hypothyroidism (CES-D p = 0.023, PCS p = 0.035), Gastroesophageal reflux disease GERD (PCS p < 0.001), Osteoarthritis (CES-D p = 0.047). Interestingly, Headache, the most frequent FM associated comorbidity in this cohort (33.6%), did not have a significant impact on the outcome domains at follow-up. Obesity (18.2%) was the only FM associated comorbidity significantly impacting all three outcome domains at follow-up. Conclusion The present study suggests that addressing obesity may significantly impact outcomes in FM patients.